Arrested Motherhood: Parenting, Cognitive Distortions, and Depressive Symptoms in Mothers Being Released from Incarceration. (3rd July 2017) - Menting, Ankie T. A.; de Castro, Bram Orobio; Matthys, Walter
SYNOPSIS: Objective. The present study examines cognitive and emotional problems in mothers being released from incarceration. Design. Participants were 98 mothers who were about to be released or had just been released from incarceration, and 63 comparison mothers from disadvantaged areas with low socioeconomic status, both with young children. Mothers provided self-report data on parenting behaviors, cognitive distortions, depressive symptoms, and socioeconomic difficulties. Results. Mothers being released from incarceration reported less optimal parenting behaviors (i.e., less involvement and poorer monitoring) and higher levels of cognitive distortions and depressive symptoms than comparison mothers. Cognitive distortions and depressive symptoms were related to less optimal reported parenting behaviors. Conclusions. Cognitive distortions, depressive symptoms, and less optimal reported parenting behaviors may be factors in incarcerated and formerly incarcerated mothers, which might put their children at risk, beyond risks associated with low socioeconomic status.